(untitled) (International Congress on Economics, Management and Business Studies, 2026)
The article analyzes the development of tourism, especially ecotourism, in Uzbekistan, its economic, ecological and social significance. It is emphasized that ecotourism plays an important role in protecting nature, increasing the income of local residents and developing sustainable tourism. At the same time, the types and conceptual approaches of ecotourism are analyzed based on international experience and scientific research. The role of innovative approaches and technological solutions in the tourism sector is also emphasized. In general, the article is devoted to the prospects for the development of ecotourism in Uzbekistan and ways to use it effectively.